Neurotransmitters, neuropeptides and calcium in oocyte maturation and early development - Alhajeri, Maitha M.; Alkhanjari, Rayyah R.; Hodeify, Rawad; Khraibi, Ali; Hamdan, Hamdan (Frontiers in Cell and Developmental Biology, 2022)
A primary reason behind the high level of complexity we embody as multicellular organisms is a highly complex intracellular and intercellular communication system. As a result, the activities of multiple cell types and tissues can be modulated resulting in a specific physiological function. One of the key players in this communication process is extracellular signaling molecules that can act in autocrine, paracrine, and endocrine fashion to regulate distinct physiological responses. Neurotransmitters and neuropeptides are signaling molecules that renders long-range communication possible. In normal conditions, neurotransmitters are involved in normal responses such as development and normal physiological aspects; however, the dysregulation of neurotransmitters mediated signaling has been associated with several pathologies such as neurodegenerative, neurological, psychiatric disorders, and other pathologies. One of the interesting topics that is not yet fully explored is the connection between neuronal signaling and physiological changes during oocyte maturation and fertilization. Knowing the importance of Ca2+ signaling in these reproductive processes, our objective in this review is to highlight the link between the neuronal signals and the intracellular changes in calcium during oocyte maturation and embryogenesis. Calcium (Ca2+) is a ubiquitous intracellular mediator involved in various cellular functions such as releasing neurotransmitters from neurons, contraction of muscle cells, fertilization, and cell differentiation and morphogenesis. The multiple roles played by this ion in mediating signals can be primarily explained by its spatiotemporal dynamics that are kept tightly checked mechanisms that control its entry through plasma membrane and its storage on intracellular stores. Given the large electrochemical gradient of the ion across the plasma membrane and intracellular stores, signals that can modulate Ca2+ entry channels or Ca2+ receptors in the stores will cause Ca2+ to be elevated in the cytosol and consequently activating downstream Ca2+-responsive proteins resulting in specific cellular responses. This review aims to provide an overview of the reported neurotransmitters and neuropeptides that participate in early stages of development and their association with Ca2+ signaling.